Synergistic interactions in two-drug and three-drug combinations (thymol, EDTA and vancomycin) against multi drug resistant bacteria including E. coli - Hamoud, Razan; Zimmermann, Stefan; Reichling, Jürgen; Wink, Michael (Phytomedicine, 2014)
Combinations of two or more drugs, which affect different targets, have frequently been used as a new approach against resistant bacteria. In our work we studied the antimicrobial activity (MIC, MBC) of individual drugs (the phenolic monoterpene thymol, EDTA and vancomycin), of two-drug interactions between thymol and EDTA in comparison with three-drug interactions with vancomycin against sensitive and resistant bacteria. Thymol demonstrated moderate bactericidal activity (MBC between 60 and 4000μg/ml) while EDTA only exhibited bacteriostatic activity over a range of 60-4000μg/ml. MICs of vancomycin were between 0.125 and 16μg/ml against Gram-positive and between 32 and 128μg/ml against Gram-negative bacteria. Checkerboard dilution and time-kill curve assays were performed to evaluate the mode of interaction of several combinations against Methicillin-resistant Staphylococcus aureus (MRSA NCTC 10442) and Escherichia coli (ATCC 25922). Checkerboard data indicate indifferent interaction against Gram-positive (FICI=1-1.3) and synergy against Gram-negative bacteria (FICI≈0.4), while time kill analyses suggest synergistic effect in different combinations against both types of bacteria. It is remarkable that the combinations could enhance the sensitivity of E. coli to vancomycin 16-fold to which it is normally insensitive. We have provided proof for the concept, that combinations of known antibiotics with modern phytotherapeutics can expand the spectrum of useful therapeutics.
Available online 18 November 2013
Gesehen am 13.10.2021